TRANSLATION AND LOCALIZATION OF E-COMMERCE PLATFORMS: A COMPREHENSIVE ANALYSIS (Ustozlar uchun, 2026)
In the era of global e-commerce, expanding into international markets requires more than simply offering products online. This article examines the role of translation and localization in creating effective, user-friendly e-commerce platforms. Translation ensures content is linguistically accurate, while localization adapts the platform to meet the cultural, economic, and social expectations of target markets. Key components of localization include currency and pricing, date and time formats, language tone, payment methods, logistics, legal compliance, and cultural elements. Technical aspects such as internationalization, content management, SEO, and quality assurance are critical for successful implementation. The article also discusses challenges, including literal translation errors, cultural differences, technical complexities, and content volume management. Real-world examples, including global platforms like Amazon and regional considerations for Uzbekistan, highlight the practical impact of localization on user experience, trust, engagement, and business growth. The findings underscore that effective translation and localization are essential strategies for e-commerce success in the global market.